Efficacy of Low Dose Oral Isotretinoin on Alternate Day Vs Pulses Regimen for Acne Vulgaris Treatment: RCT - Muhammad Dawood, Nasma Noor, Sadia Hameed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acne has a worldwide distribution with no specific predilection for any race starting in adolescence and usually resolves by mid-twenties. Aim: To compare the efficacy of low dose 1mg/kg oral isotretinoin on alternate day versus pulses of oral isotretinoin in the treatment of acne vulgaris. Study Design: Randomized control trial. Methodology: All patients (n=254) having severe facial acne vulgaris were included. Patients in group A, was given oral isotretinoin 1mg/kg on alternate day and those in group B, oral isotretinoin 1 mg/kg/day for one week/four weeks. Patients were followed up at 12 weeks to see response of each group. Response was noted in terms of more than 60% improvement in total acne load from baseline. All this information was recorded on Performa. Data was analyzed using SPSS version 26. Results were presented as frequency and percentage. Age was presented as mean± SD. Results: In group A, total acne load was decreased from a mean of 114.6 to 5.24 with 95.42% response was seen during 24 weeks of treatment .In group B total acne load was decreased from 110.4 to a mean of 22.33 with 79.77% response was seen during 24 weeks of treatment. Conclusion: It was concluded that treatment received by group A proved to be a better treatment option for acne vulgaris in comparison to treatment received by group B.